Perspektif Komunikasi Generasi Z Terhadap Pengobatan Alternatif Ningsih Tinampi yang Viral di Youtube - Prabayanti, Herma Retno; Sari, Yanuarita Kusuma Permata; Emmanuel, Patricius (representamen, 2020)
Our health is the primary key to our activeness and productivity to create something that would benefit others. Our advancement in modern medicine has greatly helped us to reinforce our health. But, despite the modern medication we now have, and the world’s health campaign, access to medication and modern healthcare can still be so hard to reach for several people in some area. One of the example of alternative medication that is now getting on trend is none other than Ningsih Tinampi from Pasuruan, East Java. Ningsih Tinampi has been practicing alternative medication for 5 years, and had published contents about the practice in her personal Youtube account, which now has gained over 1.5 million subscribers which range from the older to the younger generations, including the Z generation. This is something that we found interesting, since the Z generation, culturally speaking, is so far from practice of animism, dinamism, and any other practice that would sound irrational. The researching team wants to find out how the Z generations perceive the practice of alternative medication which has been constructed at Youtube. The method of this paper uses the study of phenomenology with a qualitative way of research. The theory of social constructionism will be used as the guiding theory and the result showed that the Z generations truly believe that the viral contents in Youtube is true and real.Keywords : New Media, Z Generation Communication, Social Constructionism, Mass Media